Pelatihan Alat Peraga Listrik Dinamis di SMA - Sholehudin Sholehudin; Putri Sri Wahyuni; Merlyne Febrian Onasis; Imas Ratna Ermawati (Joong-Ki : Jurnal Pengabdian Masyarakat, 2024)
Current education largely determines what education will be like in the future. Because education will continue forever. Current educational results determine the next regeneration of educators. The presentation of the material presented was material about static and dynamic electricity, then continued with questions and answers and demonstrations or practice. This community service aims to provide students with an understanding of the application of dynamic electricity in everyday life. Then the method used is the practical method in class or demonstration. The research results showed that students at SMA were enthusiastic about studying electricity even though they needed further assistance.